New lessons on DXA-based measurement of regional body composition in athletes - Haroon, N. N. (Journal of Clinical Densitometry, 2014)
The use of dual-energy X-ray absorptiometry (DXA) systems with fan beams in bone health started in the early 1990s. Now, DXA-based assessment of body composition is widely preferred in sports medicine and research. Assessment of body composition is used to guide selection of athletes, supervision of their performance, and training regimens and also to assess the effectiveness of performance enhancing interventions and rehabilitation process.